Determination of Digital Marketing: Influencer Marketing, Social Media and E-Commerce (Literature Review) - Setyo Widodo, Joko (Dinasti International Journal of Economics, Finance & Accounting, 2022)
The Literature Review Article Determination of Digital Marketing: Influencer Marketing, Social Media and E-Commerce is a scientific article that aims to build a research hypothesis on the influence between variables that will be used in further research, within the scope of Marketing Management. The method of writing this Literture Review article is using the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this study are: 1) Influencer Marketing is related to Digital Marketing; 2) Social Media related to Digital Marketing; and 3) E-Commerce related to Digital Marketing. Apart from these 3 exogenous variables that affect endogenous variables, there are many other factors including Video Advertising, Email Marketing, and Content variables.